TINGKAT KEBISINGAN BUNYI PESAWAT DI SEKITAR BANDAR UDARA SULTAN MAHMUD BADARUDIN II PALEMBANG - Setiawan, Andi Arif; Heriyana, Ana (Faculty of Mathematics and Natural Science, Universitas PGRI Palembang, 2016)
Air transportation activities have an impact on noise both during take off or landing. This research aimed to study the noise level at the residential area near to the Sultan of Mahmud Badarudin II airport, including: Tanjung Api-Api, Dakota and Sukamulya streets. Measurements were done in the morning, day time and afternoon. The result showed that the noise levels at Tanjung Api-api street during landing were 70,4 dBA in the morning, 70,45 dBA in the day time and 70,37 in the afternoon. While noise levels at Dakota street were measured as 62,33 dBA, 60,87 dBA and 64.44 dBA respectively in the morning, day time and afternoon. At Sukamulya street, the levels were measured as 59,47 dBA, 62,85 dBA and 59,77 dBA respectively. Mean while the noise levels during take off in the morning, day time and after noon respectively at Tanjung Api-api street were 68,17 dBA, 66,33 dBA and 68,03 dBA. At Dakota street were 63,5 dBA, 63,8 dBA and 64,03 dBA. While at Sukamulya street 61,94 dBA, 63,47 dBA and 58,97 dBA. Variance analyse (F test) found that the location of residential affect to the noise level, so that the interection between location and time. Keywords : Sound Intensity, take off, landing, morning, day time, afternoon. ABSTRAKAktivitas bidang transportasi penerbangan berdampak pada kebisingan baik pada saat terbang maupun saat mendarat. Penelitian ini bertujuan mengkaji tingkat kebisingan pada wilayah pemukiman yang berdekatan dengan Bandar Udara Sultan Mahmud Badarudi II, meliputi jalan Tanjung Siapi-api, jalan Dakota dan jalan Sukamulya. Pengukuran kebisingan dilakukan pada waktu pagi hari, siang hari dan sore hari. Hasil pengukuran menunjukan pada wilayah Jalan Tanjung Api-Api saat mendarat pada pagi hari 70,4 dBA, siang hari 70,45 dBA dan sore hari 70,37 dBA. Wilayah jalan Dakota pada pagi hari 62,33 dBA, siang hari 60,87 dBA dan sore hari 64,23 dBA. Wilayah jalan Sukamulya pada pagi hari 59,47 dBA, siang hari 62,85 dBA dan sore hari 59,77 dBA. Sedangkan pada saat lepas landas wilayah Jalan Tanjung Api-Api pada pagi hari 68,17 dBA, siang hari 66,33 dBA dan sore hari 68,03 dBA. Wilayah jalan Dakota pada pagi hari 63,5 dBA, siang hari 63,8 dBA dan sore hari 64,03 dBA. Wilayah jalan Sukamulya pada pagi hari 61,94 dBA, siang hari 63,47 dbA dan sore hari 58,97 dBA. Analisis sidik ragam (uji F) di dapatkan bahwa letak wilayah berpengaruh nyata terhadap tingkat kebisingan, begitu juga interaksi antara wilayah dan waktu berpengaruh nyata terhadap tingkat kebisingan. Kata Kunci : Intensitas Bunyi, terbang, mendarat, pagi, siang dan sore